Harti Hauora Tamariki: randomised controlled trial protocol for an opportunistic, holistic and family centred approach to improving outcomes for hospitalised children and their families in Aotearoa, New Zealand - Scott, Nina; Atatoa Carr, Polly E.; Jones, Amy R.; Sandiford, Peter; Masters-Awatere, Bridgette; Clark, Helen (Frontiers in Pediatrics, 2024)
Health and wellbeing inequities between the Indigenous Māori and non-Māori populations in Aotearoa, New Zealand continue to be unresolved. Within this context, and of particular concern, hospitalisations for diseases of poverty are increasing for tamariki Māori (Māori children). To provide hospitalised tamariki Māori, and their whānau (families) comprehensive support, a wellbeing needs assessment; the Harti Hauora Tamariki Tool (Harti tool) was developed. The purpose of this study is to determine how effective the Harti tool is at identifying wellbeing needs, ensuring the documentation of needs, enabling access to services and improving wellbeing outcomes for tamariki and their whānau. The study uses a Kaupapa Māori methodology with qualitative and quantitative methods. Qualitative methods include in-depth interviews with whānau. This paper presents an overview of a randomised, two parallel, controlled, single blinded, superiority trial for quantitative evaluation of the Harti programme, and hospital satisfaction with care survey. Participants will be Māori and non-Māori tamariki/children aged 0-4 years admitted acutely to the paediatric medical wards at Waikato Hospital, Hamilton, Aotearoa New Zealand. They will be randomised electronically into the intervention or usual care group. The intervention group will receive usual care in addition to the Harti programme, which includes a 24-section health needs assessment delivered by trained Māori navigators to whānau during their time in hospital. The primary endpoint is the relative risk of an acute hospital readmission in the 30 days following discharge for the intervention group patients compared with control group patients. Secondary outcomes include access and utilisation of preventative health services including: oral health care, general practice enrolment, immunisation, healthy home initiatives, smoking cessation and the Well Child Tamariki Ora universal health checks available free of charge for children in Aotearoa New Zealand. Randomised controlled trials are gold standard for measuring efficacy of complex multifaceted interventions and the results will provide high quality evidence for implementing the intervention nationwide. We expect that this study will provide valuable evidence for health services and policy makers who are considering how to improve the configuration of paediatric hospital services. Trial registration: Australian New Zealand Clinical Trials Registry (ANZCT R), registration number: ACT RN12618001079235.